2022
DOI: 10.1161/circulationaha.121.057021
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Patient-Reported Preprocedural Physical and Mental Health on 10-Year Mortality After Percutaneous or Surgical Coronary Revascularization

Abstract: Background: Clinical and anatomical characteristics are often considered key factors in deciding between percutaneous coronary intervention (PCI) or coronary artery bypass grafting (CABG) in patients with complex coronary artery disease (CAD) such as left-main CAD or 3-vessel disease. However, little is known about the interaction between self-reported preprocedural physical/mental health and clinical outcomes after revascularization. Methods: This subg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…Among patients with low Physical Component Summary (PCS) scores, low Mental Component Summary (MCS) scores, or both, no significant difference was seen in the 10-year mortality rate between PCI and CABG. 7 Of the 3075 patients who were treated in the SYNTAX trial, 198 (6.4%) and 1077 (35.0%) patients were included in PCI and CABG registries, respectively. The main reason for inclusion in the CABG registry was too complex coronary anatomy, while the main reason for inclusion in the PCI registry was too high risk for surgery (70.7%).…”
Section: Revascularizationmentioning
confidence: 99%
“…Among patients with low Physical Component Summary (PCS) scores, low Mental Component Summary (MCS) scores, or both, no significant difference was seen in the 10-year mortality rate between PCI and CABG. 7 Of the 3075 patients who were treated in the SYNTAX trial, 198 (6.4%) and 1077 (35.0%) patients were included in PCI and CABG registries, respectively. The main reason for inclusion in the CABG registry was too complex coronary anatomy, while the main reason for inclusion in the PCI registry was too high risk for surgery (70.7%).…”
Section: Revascularizationmentioning
confidence: 99%
“…Our group reported that pre-procedural biomarkers and patient-reported pre-procedural physical and mental health status (SF36-MCS) were associated with long-term mortality post revascularization, regardless of modality. 4 , 5 Although GGT is a poorly acknowledged prognostic factor, several epidemiological studies demonstrated an association with cardiovascular disease and mortality. 6…”
Section: Discussionmentioning
confidence: 99%
“…[23] It has been found to be valuable not only as an outcome measure but also as a predictor for multiple cardiovascular diseases. [12,[23][24][25][26] Studies have shown that changes in health status provide additional prognostic information beyond baseline measurements in patients with heart failure. [12] As a self-perceived indicator, HRQoL can be used to evaluate the broad impact of a disease on a patient and the effectiveness of interventions, which is closely related to therapeutics, but may not reflect in objective assessments, for example, the clinical impression of one's "wellness", physical capacity, or mental status.…”
Section: Introductionmentioning
confidence: 99%
“…[23] It has been found to be valuable not only as an outcome measure but also as a predictor for multiple cardiovascular diseases. [12,23–26]…”
Section: Introductionmentioning
confidence: 99%